2020
DOI: 10.1109/tmech.2020.2975578
|View full text |Cite
|
Sign up to set email alerts
|

A Sensorized Multicurved Robot Finger With Data-Driven Touch Sensing via Overlapping Light Signals

Abstract: Despite significant advances in touch and force transduction, tactile sensing is still far from ubiquitous in robotic manipulation. Existing methods for building touch sensors have proven difficult to integrate into robot fingers due to multiple challenges, including difficulty in covering multicurved surfaces, high wire count, or packaging constrains preventing their use in dexterous hands. In this paper, we present a multicurved robotic finger with accurate touch localization and normal force detection over … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…At the sensing stage, Jin et al reported a smart soft-robotic gripper system based on triboelectric nanogenerator sensors to capture the continuous motion and tactile information for soft gripper control, where PCA and SVM were used to realize real-time prediction [ 260 ]. Data- or AI-driven approaches can also be found in other touch/haptic/force sensing for obtaining better system understanding and task performance [ 280 , 281 , 282 ]. One level higher, at the controller stage, Verner et al implemented online reinforcement learning via a fabricated digital twin, to enable a humanoid robot to lift a weight of unknown mass through autonomous trial-and-error search [ 261 ].…”
Section: Advanced Roboticsmentioning
confidence: 99%
“…At the sensing stage, Jin et al reported a smart soft-robotic gripper system based on triboelectric nanogenerator sensors to capture the continuous motion and tactile information for soft gripper control, where PCA and SVM were used to realize real-time prediction [ 260 ]. Data- or AI-driven approaches can also be found in other touch/haptic/force sensing for obtaining better system understanding and task performance [ 280 , 281 , 282 ]. One level higher, at the controller stage, Verner et al implemented online reinforcement learning via a fabricated digital twin, to enable a humanoid robot to lift a weight of unknown mass through autonomous trial-and-error search [ 261 ].…”
Section: Advanced Roboticsmentioning
confidence: 99%
“…By utilizing the now‐available processing power, sensors and software can extract far more information than in previous eras. This is another pivotal advance that allows for innovations such as the robotic finger touch sensor enabled by neural networks and measuring overlapping optical signals in Piacenza et al [ 161 ] Such an example shows that, by training, many different signals from a host of sensors, not necessarily optical, can be interpreted as a single action or quantity. This processing power also enables more efficient human‐machine interfaces such that researchers can collect, and make sense of, data sets on the human body at large scales.…”
Section: Looking Forwardmentioning
confidence: 99%
“…Fortunately, a large number of compelling tactile sensors have been developed for robotic applications, including the GelSight (Yuan et al, 2017), TacTip (Ward-Cherrier et al, 2018), Soft-bubble (Alspach et al, 2019), DIGIT Lambeta et al (2020), overlapping optical signal sensors (Piacenza et al, 2020), and commercial offerings from SynTouch, Pressure Profile Systems, ATI Industrial Automation, and OnRobot. For recent comprehensive reviews, see Dahiya et al (2010), Yousef et al (2011), Kappassov et al (2015), Chen et al (2018), and Yamaguchi and Atkeson (2019).…”
Section: Introductionmentioning
confidence: 99%